Efficacy of Controlled Whole-Body Vibration Training on Improving Fall Risk Factors in Stroke Survivors: A Meta-analysis. (April 2020) - Yang, Feng; Butler, Andrew J.
Background . Controlled whole-body vibration (CWBV) training has been applied to people with stroke. However, it remains inconclusive if CWBV reduces fall risk in this population. Objective . To (1) assess the immediate and retention effects of CWBV training on fall risk factors in people at postacute and chronic stages of stroke and (2) examine if CWBV dosage is correlated with the effect size (ES) for 3 fall risk factors: body balance, functional mobility, and knee strength. Methods . Twelve randomized controlled trials were included. ES was calculated as the standardized mean difference, and meta-analyses were completed using a random-effects model. Results . CWBV training may lead to improved balance and mobility immediately after training (ES = 0.27, P = .03 for balance; ES = 0.34, P = .02 for mobility) but not at the 3-month follow-up test (ES = 0.02, P = .89 for balance; ES = 0.70, P = .11 for mobility). CWBV affects knee strength capacity with mild ES (ES = 0.08 and 0.11, respectively, for immediate and retention effect; P ≥ .68 for both). Metaregression indicated that the immediate ES is strongly correlated with training dosage for balance ( r = 0.649; P = .029) and mobility ( r = 0.785; P = .036). Conclusions . CWBV training may benefit balance and mobility immediately, but the training effect may not persist among people with stroke. Additionally, the CWBV dosage correlates with the ES for body balance and mobility. More high-quality studies are needed to determine the retention effects of CWBV training.